LINGUISTIC PRINCIPLES OF INTERPRETING THE PHRASEOSTYLISTIC MEANING OF FIXED PHRASEOLOGICAL UNITS WITHIN TEXTUAL CONTEXTS (SCIENCE TIME JOURNAL, 2026)
This article examines the phraseostylistic meaning of fixed phraseological units in English as a linguistic phenomenon formed and realized within textual boundaries. The study proceeds from the assumption that the stylistic and pragmatic potential of phraseological units is not inherent in isolation but is determined by their functioning in specific textual environments. Particular attention is given to context as the principal factor that actualizes emotional-expressive and evaluative components of phraseological meaning. Based on material from English literary prose, the article identifies the key linguistic principles underlying the emergence and interpretation of phraseostylistic meaning, including contextual determination, semantic transformation, pragmatic actualization, discursive adaptability, and cultural-cognitive grounding. The findings contribute to a clearer understanding of phraseological units as dynamic elements of discourse and as important stylistic resources in literary texts.